Synthesis, Analytical Characterization, and Human CB1 Receptor Binding Studies of the Chloroindole Analogues of the Synthetic Cannabinoid MDMB-CHMICA - Sascha Münster-Müller; Steven Hansen; Tobias Lucas; Arianna Giorgetti; Lukas Mogler; Svenja Fischmann; Folker Westphal; Volker Auwärter; Michael Pütz; Till Opatz (Biomolecules)
Synthetic cannabinoids (SCs) are one of the largest groups of new psychoactive substances (NPSs). However, the relationship between their chemical structure and the affinity to human CB1 receptors (hCB1), which mediates their psychotropic activity, is not well understood. Herein, the synthesis of the 2-, 4-, 5-, 6- and 7-chloroindole analogues of the synthetic cannabimimetic MDMB-CHMICA, along with their analytical characterization via ultraviolet–visible (UV/VIS), infrared (IR), nuclear magnetic resonance (NMR) spectroscopy, and mass spectrometry, is described. Furthermore, all five derivatives of MDMB-CHMICA were analyzed for their hCB1 binding affinities. Chlorination at position 4 and 5 of the indole core reduced the binding affinity compared to MDMB-CHMICA, while the test compounds chlorinated in positions 2, 6, and 7 largely retained their binding affinities relative to the non-chlorinated parent compound.